Everything is Possible on Social Media: Using Instagram as an Eco-print Marketing Media in Serang Village, Purbalingga Regency - Dewi, Reni Shinta; Budiatmo, Agung; Purbawati, Dinalestari; Chairina, Soraya (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The study aims to address the impact of the COVID-19 pandemic on sectors including eco-print products produced by Gallery Yupa Eco-print in Purbalingga. The shift in consumer behavior from offline to online has posed challenges such as the halt of exhibition activities, preventing the introduction of products to potential consumers. Method: The service activities carried out by the Undip PKUM (Strengthening Community Leading Commodities) Team involve providing Digital Marketing training and assistance, particularly on Instagram social media. The Participatory Rural Appraisal (PRA) approach is used in this activity, which is a method for studying rural conditions and life from, with, and by village communities. Practical Applications: The training and assistance aim to increase consumer awareness, especially introducing Eco-print as a unique and environmentally friendly contemporary handicraft. This approach is considered appropriate as it empowers the community to independently solve the problems they face. Conclusion: As a result of the PKUM service activities, Gallery Yupa Eco-print was able to promote their products via social media, specifically Instagram, and began to gain awareness from consumers or potential customers. This indicates the effectiveness of the implemented methods in addressing the challenges posed by the pandemic.